SISTEM PENGGERAK GONDOLA DENGAN MENGGUNAKAN HANDPHONE - Susila, Tjandra; Setyaningsih, Endah; Soedjaya, Pranata (Universitas Tarumanagara, 2008)
Gondola is a human technology used to clean the glass windows building facade. However, in many uses an accident victim who pluck the soul because of various factors, among other natural factors or human negligence itself Gondola that design is a